Influence of compression garments on fatigue behaviour during running based on nonlinear dynamical analysis - Bajelani, K.; Arshi, A. R.; Akhavan, A. N. (Sports Biomechanics, 2022)
The purpose of this study was to assess quantitatively the effects of compression garments (CGs) on fatigue behaviour during sport activities such as running, which are the subject of a series of qualitative and physiological studies. A quantitative biomechanical analysis of the effects of CGs could assist coaches and athletes to adopt these types of performance enhancement garments. In this research, kinematic changes are measured using 2D phase portraits to study the influence of CGs on fatigue behaviour. Fifteen healthy male intermediate athletes participated in this study and the kinematic data of hip repetitive movements with and without CG were measured during running tasks. These data are used to reconstruct the state space and the local flow variation method is adopted to quantify the trajectory drifts caused by fatigue in the state space. The effects of CGs on the complexity of kinematic changes are also evaluated using permutation entropy. The results indicate that fluctuations in the kinematics are reduced when compression garments are used. It is also shown that adoption of CGs results in a reduction of the rate of fatigue development and decreased complexities in the movement kinematics.